Penerapan Model Inquiry Learning berbantuan Media Auvipow terhadap Pemahaman Konsep Matematika pada Siswa SD - Handayani, Syahruni Fariha; Riswari, Lovika Ardana; Santoso, Denni Agung (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2025)
The background of this study is based on the low level of students' understanding of mathematical concepts, which is indicated by their difficulty in connecting concepts with applications in everyday life. This study aims to determine how effective the Inquiry Learning model using Auvipow media is in improving students' understanding of mathematical concepts in elementary school. This study uses a quantitative approach with a pre-experimental design called one group pretest-posttest. The subjects of the study were fifth-grade students of SDN 2 Undaan Lor. The research sampling technique was carried out using total sampling. The tool used was a concept understanding test in the form of essay questions. The results of the study showed an increase in the average score between the pretest and posttest after the application of the Inquiry Learning model with the help of Auvipow media. While data analysis used data normality tests and paired t-tests to test the research hypothesis. The data analysis technique used the N- Gain test and the Paired sample t-test. The results showed that the average score obtained by fifth-grade students in the pretest was 53.61 and the posttest was 76.33. The results of data analysis using SPSS Statistics 25 obtained an N-Gain score of 0.7500, which is categorized as high. Meanwhile, the Paired sample t-test showed a sig. (2-tailed) value of 0.000 0.05, meaning there is a difference in the average. Therefore, it can be concluded that the Inquiry Learning model with the help of Auvipow media is effective in improving students' understanding of mathematical concepts in elementary school.